The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1101/2022.08.23.504923
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The aperiodic exponent of subthalamic field potentials reflects excitation/inhibition balance in Parkinsonism: a cross-species study in vivo

Abstract: Periodic features of neural time series data, such as local field potentials (LFP), are often quantified using power spectra. While the aperiodic exponent of spectra is typically disregarded, it is nevertheless modulated in a physiologically-relevant manner and was recently hypothesised to reflect excitation/inhibition (E/I) balance in neuronal populations. Here, we used a cross-species in vivo electrophysiological approach to test the E/I hypothesis in the context of experimental and idiopathic Parkinsonism. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…Recently, the aperiodic exponent (1/F slope of the PSD) was suggested as a marker for E/I balance 24,26,27 . We extracted the aperiodic exponent between 5 and 50 Hz to avoid a spectral plateau at ~50 Hz and found that aperiodic exponents in STN increase with increasing DBS currents (Linear mixed‐effect model (LME): estimate = 0.006, t = 8.15, P < 0.001, n = 11 hemispheres), consistent with the hypothesis that high‐frequency stimulation inhibits STN (Fig.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Recently, the aperiodic exponent (1/F slope of the PSD) was suggested as a marker for E/I balance 24,26,27 . We extracted the aperiodic exponent between 5 and 50 Hz to avoid a spectral plateau at ~50 Hz and found that aperiodic exponents in STN increase with increasing DBS currents (Linear mixed‐effect model (LME): estimate = 0.006, t = 8.15, P < 0.001, n = 11 hemispheres), consistent with the hypothesis that high‐frequency stimulation inhibits STN (Fig.…”
Section: Resultssupporting
confidence: 83%
“…The lower bound was selected to avoid the impact of low‐frequency oscillations, and the upper bound was selected to avoid the impact of spectral plateaus at high DBS intensity 23 . The same FoooF settings were used to identify meaningful changes in the aperiodic exponent of STN‐LFPs with dopaminergic medication and high‐frequency stimulation 24 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations